CO2 electro/photocatalytic reduction using nanostructured ZnO and silicon-based materials: A short review - Galdámez-Martínez, Andrés; Dutt, Ateet (Nanofabrication, 2023)
Reducing CO2 net emissions is one of the most pressing goals in tackling the current global warming emergency. Therefore, the development of carbon recycling strategies has resulted in the application of heterogeneous catalysts toward the electro/photocatalysis reduction of CO2 into hydrocarbons with potential reusability. Their morphology is among the properties that affect the performance and selectivity of catalysts towards this reaction. Nanostructuring methods offer popular strategies for catalytic applications since they allow an increase in the area/volume ratio and versatile control over surface physicochemical properties. In this review, we summarize studies that report the use of versatile synthesis techniques for obtaining nanostructured metallic and semiconductor materials with application in the electro/photocatalytic reduction of CO2. Enhancing mechanisms to the catalytic CO2 reduction yield, such as improved charge carrier separation efficiency, defect engineering, active site concentration, and localized plasmonic behavior, are described in conjunction with the control over the morphologies of the nanostructured platforms. Special attention is given to ZnO and silicon-based matrices as candidates for developing abundant and non-toxic catalytic materials. Therefore, this work represents a guide to the efforts made to design electro/photocatalytic systems that can contribute significantly to this field.